Synthesis and Application of Coconut Shell Activated Carbon Fe3O4 Composite for Zn2+ Metal Ion Adsorption from Wastewater - Wahyu Triaji Rahadianto; Heni Sugesti; Yogi Chandra (Equilibrium Journal of Chemical Engineering, 2026)
Abstract. Industrial wastewater containing heavy metals such as Zn²⁺ ions is one of the hazardous pollutants that can pose serious risks to the environment and human health. The presence of Zn²⁺ in aquatic systems at high concentrations can lead to acute toxicity, thus requiring effective and sustainable treatment methods. Adsorption has become one of the most widely developed treatment approaches due to its advantages, including high efficiency, low operational cost, and environmental friendliness. This study aims to synthesize and characterize Fe₃O₄/activated carbon composites as adsorbents for the removal of Zn²⁺ ions from wastewater. Fe₃O₄ was synthesized through a coprecipitation method using FeCl₃·6H₂O and FeSO₄·7H₂O precursors, and subsequently combined with thermally activated coconut-shell carbon to enhance surface area and adsorption capacity. The composite was characterized using X-Ray Diffraction (XRD). Adsorption tests were conducted using various composite masses 0.04 g, 0.05 g, 0.06 g, 0.07 g, and 0.08 g to examine the effect of adsorbent dosage. The best performance was obtained at an adsorbent mass of 0.08 g with an optimum contact time of 75 minutes. Under these conditions, an initial Zn²⁺ concentration of 30 ppm decreased significantly, achieving a maximum removal efficiency of 91% and 84.63% under other test conditions. These findings indicate that the Fe₃O₄/activated carbon composite exhibits high effectiveness and selectivity in adsorbing Zn²⁺ ions and holds strong potential for development as a wastewater treatment material based on renewable and environmentally friendly local resources.Keywords: Activated Carbon, Adsorption, Coconut Shell, Fe₃O₄ Composite, Zn²⁺ Ions